(untitled) (TAJ: Journal of Teachers Association, 2009)
An ORT (Oral Rehydration Therapy) Corner was set up in Rajshahi Medical College in July 1990. 4267 Patients aged between 0-12 years who attended the ORT corner of the diarrhoeal training unit in the year of 2003 were studied to find out the impact of this unit in the management of diarrhoeal diseases in children and its effect on diarrhoeal admission in the hospital. 53.56% (2285) of them were male and 46.21% (1972) were female. Only 1.54% (66) of the patient who attended the ORT Corner needed hospital admission. 78.72% Patients were under 5 year of age and 90.57% (3865) patients had no dehydration (group-A) and they were sent home with ORS (Oral Rehydration Solution) and necessary advice. 8.3% (355) patients had some dehydration (Group -B) and they were treated at the ORT corner with ORS for 2-6 hours and sent home after initial rehydration. But 19 (0.44%) patients had needed hospital admission later due to failure of ORS treatment. 47 (1.10%) Patient had severe dehydration (Group-C), who had persistent diarrhoea and immediately admitted in Paediatric unit and given necessary treatment. Total diarrhoeal admission in indoor was 74 in 2002 and 66 in 2003 and a significant reduction in admission was observed during the study period from that of the previous year. (p < 0.01). It was concluded that the ORT corner was vary effective simple and safe in the management of diarrhoea in children and reduced the number of diarrhoeal admissions in the hospital. doi: 10.3329/taj.v20i1.3090 TAJ 2007; 20(1): 52-55